FUNGSI DAN MAKNA TRADISI GENJEK KARANGASEM - Ida Bagus Nyoman Mantra (SPHOTA: Jurnal Linguistik dan Sastra, 2016)
Abstract The present study aimed at investigating the oral tradition of genjek Karangasem with the main attempt was to analyze the various functions and meanings of genjek Karangasem. The theory of literary function utilised in the present study was the theory as suggested by Bascom in Sukatman (2011:11) and semiotics theory as suggested by Van Zoest (1993:131). The theory of literary function was utilized to anlyse the function of genjek Karangasem and semiotics theory was used to examine the meaning of genjek Karangasem. The present study was a qualitative study with systematic descriptive analysis which departs from theory to the observation of valid and reliable data. The approach used in this study was a phenomenological approach that moved from the phenomenon of language used in genjek Karangasem. The implication of this study was expected to provide benefits to the development of linguistics studies and the understanding of function and meaning of the other oral traditions as well as other literary works for the sake of the betterness of social life improvement. The present study revealed that the function of genjek Karangasem were functions to remember the past, education, entertainment, ethnic solidarity, social control, social protest, and the religious function, meanwhile, the meanings found in genjek Karangasem, such as the meaning of love, ritual, recognition of the existence of social stratification, and the meaning of the collective consciousness. Keywords: Function, Meaning, Genjek